Utilization of Leaf Water Lettuce (Pistia stratiotes L) Meal Fermentation Using Cow Rumen Fluid in Diet on Growth of River Corp (Leptobarbus hoevenii) Fingerling - Novendri, Rizki; Suharman, Indra; ', Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted for 56 days from September – November 2016. The aim of this research to determine the number of leaves water lettuce meal fermented in fish feed formulation River Corp (Leptobarbus hoevenii) the effect on growth, feed efficiency and protein retention. This study uses a completely randomized design (RAL) with one factor, 5 level treatments and 3 replications. The fish used in this research with size 7-9 g in weight. Treatments with water lettuce leaves meal fermentation P0 (0%), P1 (10%), P2 (20%), P3 (30%), P4 (40%) with feed protein content of 24,75%. The results showed that fermentation of water lettuce leaves have significant effect (P<0,05) on growth, feed efficiency and protein retention. Replacement 40% of water lettuce fermentation produced highest digestibility 66,83%, feed efficiency 8,70%, protein retention 12,63% and spesific growth rate 0,67%.Keywords: Leptobarbus hoevenii, Water Lettuce Leaves, Fermentation, Rumen Fluid